1990
DOI: 10.1136/bmj.300.6737.1458
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to chemotherapy: comparing views of patients with cancer with those of doctors, nurses, and general public.

Abstract: Objective-To compare responses of patients with cancer with those of a matched control group, cancer specialists, general practitioners, and cancer nurses in assessing personal cost-benefit of chemotherapy.Design-Prospective study of consecutively recruited patients with cancer and other groups by questionnaire; half of the patients received the questionnaire again three months after starting treatment.Setting-A medical oncology ward of a London teaching hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
334
4
23

Year Published

1992
1992
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 710 publications
(376 citation statements)
references
References 6 publications
15
334
4
23
Order By: Relevance
“…However, in a study based on hypothetical treatment scenarios, patients with cancer who were about to undergo chemotherapy were asked to balance the price they would be prepared to pay in terms of side-effects for a particular degree of benefit. About half of patients reported they would accept intensive toxic chemotherapy for minimal benefit in terms of survival, prolongation of life or relief of symptoms (Slevin et al, 1990). This is a hypothesis-generating study.…”
Section: Discussionmentioning
confidence: 96%
“…However, in a study based on hypothetical treatment scenarios, patients with cancer who were about to undergo chemotherapy were asked to balance the price they would be prepared to pay in terms of side-effects for a particular degree of benefit. About half of patients reported they would accept intensive toxic chemotherapy for minimal benefit in terms of survival, prolongation of life or relief of symptoms (Slevin et al, 1990). This is a hypothesis-generating study.…”
Section: Discussionmentioning
confidence: 96%
“…We observed similar findings in that most patients rated highly the possibility of personal benefit. Slevin et al (1990) found that patients with cancer are willing to accept treatment with cytotoxics for lower chances of benefit than those thought acceptable by their physicians or nurses.…”
Section: Discussionmentioning
confidence: 99%
“…All patients will experience the side effects, but only some patients will actually benefit from this treatment. Patients' preferences regarding this trade-off have shown to vary widely (e.g., Jansen et al, 2001) and to differ from the preferences of doctors (e.g., Slevin et al, 1990). Charles et al (1997) stress the importance of shared decision-making in the case of adjuvant chemotherapy, because: (1) several treatment options exist with different possible outcomes and substantial uncertainty, (2) there is often no clear-cut right or wrong answer and (3) the impact of the treatment on the patient's physical and psychological well being will vary.…”
mentioning
confidence: 99%